Protective effect of raloxifene on lipopolysaccharide and acid- induced acute lung injury in rats - Zhou Guang-ju; Zhang Hong; Zhi Sheng-de; Jiang Guo-ping; Wang Jing; Zhang Mao; Gan Jian-xin; Xu Shao-wen; Jiang Guan-yu (Acta Pharmacologica Sinica, 2016)
Aim: To evaluate the protective effect of oral raloxifene on acute lung injury. Methods: Thirty adult, male Sprague-Dawley rats each weighing 180–210 g were used and divided into 3 groups: the raloxifene-lipopolysaccharide (LPS)-HCl group (n=10), the LPS-raloxifene-HCl group (n=10), and the placebo group (n=10). All the rats were injected intraperitoneally (ip) with 5 mg/kg LPS, and raloxifene (30 mg/kg) was orally administered 1 h before and 14 h after LPS injection into the raloxifene-LPS-HCl and the LPS-raloxifene-HCl groups, respectively; the placebo group received nothing. Sixteen hours after LPS injection, all the animals were anesthetized and the femoral artery was cannulated. All the rats received a direct intratracheal (IT) injection of HCl (pH 1.2; 0.5 mL/kg). The mean arterial pressure (MAP) and blood gas concentrations were measured. Fifteen rats (5 in each group, respectively) underwent a micro positron emission tomography (microPET) scan of the thorax 4 h after HCl instillation. The wet/dry (W/D) weight ratio determination and histopathological examination were also performed. Results: The rats in the LPS-raloxifene-HCl group had a lower [18F]fluorodeoxyglucose uptake compared with the rats in the placebo group (4.67plusminus1.33 vs 9.01plusminus1.58, respectively, P